Słowniczek wyrazów weterynarskich wobec polskiej terminologii weterynarynej w Słowniku terminologii lekarskiej polskiej - Jankowiak, Lucyna Agnieszka (Slavia Occidentalis, 2023)
The aim of the article is to compare materials from two 19th-century dictionaries that comprise Polish veterinary terminology: Słowniczek wyrazów weterynarskich of 1876 and Słownik terminologii lekarskiej polskiej of 1881. In the dictionary of 1881 there are 284 entries out of 297 contained in the lexicon of 1876. Of these, only 258 entries are full entries. The comparison of their editing in both dictionaries shows that in the lexicon of 1881, 3 foreign headwords had fewer Polish equivalents, 21 had more Polish terms, and 228 had the same number of Polish equivalents. The quantitative changes in the last two groups were accompanied by qualitative changes, involving the replacement of Polish terms. The analysis of Polish veterinary terminology has also shown its strong connections with Polish medical terminology of the time.